Impact of MSIB Program on the Personal Development of Students at Universitas Muhammadiyah Surakarta - Ardani, Amanda Putri; Suranto, Suranto (Graduate Program Magister Manajemen Pendidikan, 2025)
The Magang dan Studi Independen Bersertifikat (MSIB) program, initiated by Indonesia’s Ministry of Education, Culture, Research, and Technology in 2021, provides students with opportunities to gain hands-on experience in the professional world. This study aims to determine the impact of MSIB on the personal development of Universitas Muhammadiyah Surakarta (UMS) students in 2023. Employing a descriptive qualitative approach, data were gathered through interviews, observations, and documentation involving 10 UMS participants. Thematic descriptive analysis, validated through data triangulation, revealed significant positive impacts on students’ personal growth. The category of improved personal development is divided into four, namely: 1) improved personal development in working knowledge, 2) improved personal development in work skills, 3) improved personal development in work commitment, and 4) improved personal development in professional relationships. This research highlights MSIB’s role in fostering student development and bridging academic learning with industry demands, positioning it as a transformative higher education model.